The Impact of Family Conflict on the Development of the Mulya Manggis Family Business - Irvan Juliyano; Citra Putri Desmona; Rifan Irawan; Mira Nurfitriya; Azizah Fauziyah (Proceedings Series on Social Sciences & Humanities, 2024)
Family businesses have unique characteristics as they are owned and managed by family members. However, family businesses also have unique challenges, such as family conflicts that have an impact on business development. This study aims to determine the impact of family conflict on the development of the Mulya Manggis family business. The object of this research is the Mulya Manggis family business. The method to be used in this research uses quantitative research methods with a descriptive verification approach in the form of interviews conducted in private and filling out questionnaires. The population used is Mulya Manggis family members and the sample used is family members who are directly involved in the Mulya Manggis family business. The alleged results of this study indicate that the impact of family conflict has significant negative implications for the development of family businesses.